2021
DOI: 10.3389/fpubh.2021.638430
|View full text |Cite
|
Sign up to set email alerts
|

Public Knowledge, Attitudes, and Practices Behaviors Towards Coronavirus Disease 2019 (COVID-19) During a National Epidemic—China

Abstract: Background: The rapid outbreak of coronavirus disease 2019 (COVID-19) posed a serious threat to China, followed by compulsive measures taken against the national emergency to control its further spread. This study was designed to describe residents' knowledge, attitudes, and practice behaviors (KAP) during the outbreak of COVID-19.Methods: An anonymous online questionnaire was randomly administrated to residents in mainland China between Mar 7 and Mar 16, 2020. Residents' responses to KAP were quantified by de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 17 publications
0
11
0
1
Order By: Relevance
“…Furthermore, this willingness to pay for vaccine also depends on other different factors including employment status and preexistence chronic diseases [52]. Additionally, raising the public awareness, and enhancing the knowledge about the disease risk may create more responsible behavior among the public [53]. These interventions would increase the vaccine acceptance rate.…”
Section: Covid-19 Vaccine Acceptance Rate Variation Between Countriesmentioning
confidence: 99%
“…Furthermore, this willingness to pay for vaccine also depends on other different factors including employment status and preexistence chronic diseases [52]. Additionally, raising the public awareness, and enhancing the knowledge about the disease risk may create more responsible behavior among the public [53]. These interventions would increase the vaccine acceptance rate.…”
Section: Covid-19 Vaccine Acceptance Rate Variation Between Countriesmentioning
confidence: 99%
“…Having a health literacy about COVID-19 was another determinant of women's observance of health protocols. In most studies, health literacy in the field of COVID-19 has been reported as one of the most important reasons for compliance or non-compliance with health protocols (34)(35)(36). In fact, the more people know about prevention methods and how to follow health protocols, the more they are encouraged to follow these protocols.…”
Section: Discussionmentioning
confidence: 99%
“…(1) The COVID-19 pandemic spreads quickly from person to person and has no symptoms in the early stages, with an average incubation period of 5 days [22], making early diagnosis and isolation difficult.…”
Section: Discussionmentioning
confidence: 99%